Internet of Things (IoT) Application in Meliponiculture - Md Yunus, Mohd Amri (International Journal of Integrated Engineering, 2017)
This paper presents an investigation on the environmental factors affecting meliponiculture (the cultivation of stingless bees on a commercial scale for honey production or pollination) using an internet of thing (IOT) application. Manual collection of data for chosen factors can be sporadic and produce variations from incorrect measurement taking; this can cause complications in producing any important interpretation. The feasibility of online monitoring of bee hive based on IoT application has not been properly explored. For a particular bee hive, the amount of departing and arriving bee was estimated by using non-intrusive sensors of infrared transmitter and receiver. A basic temperature-humidity sensor to monitor the temperature and humidity was placed inside the bee hive.Â  All sensors were integrated with a microcontroller and a Wi-Fi module which sent the data wirelessly to IoT cloud platform where the data was continuously saved, monitored, and can be retrieved anytime. Colonies of Trigona Itama were active throughout the whole period at the experimental site but the daily activity period was intense in the warmer days (over 30 Â°C) whereas the relative humidity had no significant effect on the flight activities. Intensity of daily flight activity was greatest in December, 2016. Temperature was the most important variable affecting flight.